Optimal design configuration and operating sequencing of hybrid chiller plant: A case study of hotel building in Cairo, Egypt. (October 2021) - Mouneer, Tarek A.; Aly, Mohamed H.; Mina, Ehab M.
Abstract: This research demonstrates the optimal design option and operating sequencing for hybrid chillers plant which can use two different energy sources. The purpose of the investigation focus on Sofitel Cairo Nile El-Gezirah Hotel, nestled within Al-Zamalek island in Cairo, Egypt, as a case study in current research. Special attention is given to its round façade which gives special characterised cooling load profiles. The study compromises two main design configurations from A.I to A.V with 5 options and from B.I to B.VI with 6 options, to investigate and compare several operating sequences for hybrid chiller plant (HCP) of 4000 TR. The first investigation employs systematic calculation for the initial and running costs of the HCP with design configurations A and B. The second investigation compares their several operating sequences for design configurations A and B. The results of performance parameters such as coefficient of performance for hybrid chiller plant records variations in the running cost using hourly analysis from time 00:00 to 23:59 in response of variation in solar radiation, external loads, and internal loads. Concerning the results of these two analyses, the finding depicts the optimal design configuration, besides the best operating sequence for each design configuration regarding the estimated operational data for each design option and operating sequence under the building applied cooling loads during the summer season with Cairo climate conditions. Graphical abstract: Image 1 Highlights: This study developed a deep understanding for hybrid chiller plant performance. The hybrid chiller plant effects of running cost in hotel buildings were investigated by quantitative analysis. The hybrid chiller plant significantly improved the performance of chiller plant by reducing running cost. The findings can contribute to air conditioning system designers and hotel building operators. Factors affect in hybrid chiller plant in hotel building are reviewed.